Aktuele kunst Aalst. - Galle, Marc (Aalst : Oud Hospitaal Aalst)
Van der Elst, Dirk ; Van Holsbeek, Herwig ; Van Hoorick, Annemie ; Wauters, Marcel ; Triest, Adolf ; Nicolas ; Mechnig, Karel ; De Neve, Vik ; De Moor, Liliane ; Boon, Louis-Paul ; Bekaert, René ; Baeyens, Martin R.
biografie
Aktuele kunst Aalst, Oud Hospitaal, Aalst, 27 maart - 12 april s.a.
Nederlands
boek